The Ways to Depict the Inner-Thoughts of Obeying Woman of the Story “Weekend” By Fay Weldon - Shalola, Davletova (International Journal on Integrated Education, 2023)
Feminism has been becoming one of the most controversial topics for many years in the History of European Literature. Hence, a myriad of authors released their masterpieces depicting social issues of this contemporary epoch in terms of the way treating females by the members of the opposite gender. This article is partly about a woman who dedicated herself to her immediate family members forgetting about her self-values and self -esteem and mostly about the literary devices the author uses to boost the hues of her writing style.